Anode composition, anode for lithium secondary battery including the same, and lithium secondary battery including the anode
Patent Information
- Application Number
- JP2024547582
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-09-05
- Filing Date
- 2023-09-06
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2043-09-06
AI Technical Summary
【0017】 本出願に係る負極組成物の場合、負極の容量増加のために、シリコン系活物質を含み、かつ、線状導電材を含むことで、前述した問題を解決した。具体的に、短距離の導電ネットワークを満たすことができるMWCNTと、長距離およびバインダーの剛性を高めることができるSWCNTとを用いたものであり、前記の組成を満たす導電材を用いて負極組成物中の活物質の割合を高め、負極スラリーの固形分を高めることができるため、セル自体の性能を改善できるという特徴を有することになる。
Smart Images

Figure 2025506497000001_ABST
Abstract
Description
[Technical field]
[0001] This application claims the benefit of the filing date of Korean Patent Application No. 10-2022-0113646 filed with the Korean Intellectual Property Office on September 7, 2022, the entire contents of which are incorporated herein by reference.
[0002] The present application relates to a negative electrode composition, a negative electrode for a lithium secondary battery including the same, and a lithium secondary battery including the negative electrode. [Background technology]
[0003] The rapid increase in the use of fossil fuels has led to an increased demand for alternative and clean energy, and one of the most actively researched fields in this area is the field of power generation and storage using electrochemical reactions.
[0004] At present, a representative example of an electrochemical element that uses such electrochemical energy is a secondary battery, and the range of its use is tending to expand more and more.
[0005] As technological development and demand for mobile devices increases, the demand for secondary batteries as energy sources is rapidly increasing. Among such secondary batteries, lithium secondary batteries, which have high energy density and voltage, long cycle life, and low self-discharge rate, have been commercialized and are widely used. In addition, research into methods for manufacturing high-density electrodes with higher energy density per unit volume as electrodes for such high-capacity lithium secondary batteries is being actively conducted.
[0006] In general, a secondary battery is composed of a positive electrode, a negative electrode, an electrolyte, and a separator. The negative electrode contains a negative electrode active material that inserts and removes lithium ions released from the positive electrode. Silicon-based particles having a large discharge capacity can be used as the negative electrode active material.
[0007] In particular, with the recent demand for high-density energy batteries, active research is being conducted into methods of increasing capacity by using silicon-based compounds such as Si / C and SiOx, which have a capacity 10 times larger than that of graphite-based materials, as negative electrode active materials. However, although silicon-based compounds, which are high-capacity materials, have a larger capacity than the conventionally used graphite, they have the problem that their volume expands rapidly during charging, cutting off the conductive path and reducing the battery characteristics.
[0008] In order to solve the problems associated with using silicon-based compounds as negative electrode active materials, various methods have been discussed, such as a method of adjusting the driving potential, a method of additionally coating a thin film on the active material layer, a method of controlling the particle size of the silicon-based compound, and other methods of suppressing the volume expansion itself or preventing the conductive path from being broken. However, the above methods have limitations in their application because they may actually degrade the performance of the battery, and there are still limitations in the commercialization of negative electrode batteries with a high content of silicon-based compounds.
[0009] Therefore, in the process of preparing a silicon-based negative electrode for maximizing capacity characteristics, research is needed on a negative electrode composition that can prevent the volume expansion, destruction of the conductive path, and surface cracking phenomena caused by charging and discharging. [Prior art documents] [Patent documents]
[0010] [Patent Document 1] JP 2009-080971 A Summary of the Invention [Problem to be solved by the invention]
[0011] In silicon-based negative electrodes, negative electrode binders are used to suppress volume expansion due to charging and discharging, and various types of negative electrode conductive materials are used to maintain the conductive path. However, the problems of volume expansion due to charging and discharging and life characteristics have yet to be solved.
[0012] As a result of research to improve the above problems, it has been found that when a conductive material having a certain composition is included as a conductive material and the content of the binder is adjusted, it can be controlled.
[0013] Therefore, the present application relates to a negative electrode composition capable of solving the above problems, a negative electrode for a lithium secondary battery including the same, and a lithium secondary battery including the negative electrode.
Means for Solving the Problems
[0014] One embodiment of the present specification is a negative electrode composition including a silicon-based active material; a linear conductive material; and a negative electrode binder, wherein the silicon-based active material includes one or more selected from the group consisting of SiOx (x = 0) and SiOx (0 < x < 2), and includes 90 parts by weight or more of the SiOx (x = 0) based on 100 parts by weight of the silicon-based active material, the linear conductive material includes SWCNT; and MWCNT, and includes 80 parts by weight or more and 95 parts by weight or less of the silicon-based active material based on 100 parts by weight of the negative electrode composition, and includes 3 parts by weight or more and 10 parts by weight or less of the negative electrode binder based on 100 parts by weight of the silicon-based active material.
[0015] Another embodiment provides a negative electrode for a lithium secondary battery including a negative electrode current collector layer; and a negative electrode active material layer including the negative electrode composition according to the present application formed on one or both surfaces of the negative electrode current collector layer.
[0016] Finally, a lithium secondary battery is provided, including a positive electrode; a negative electrode for a lithium secondary battery according to the present application; a separator provided between the positive electrode and the negative electrode; and an electrolyte.
Effects of the Invention
[0017] In the case of the negative electrode composition according to the present application, the above-mentioned problem is solved by including a silicon-based active material and a linear conductive material to increase the capacity of the negative electrode. Specifically, MWCNTs that can fill a short-distance conductive network and SWCNTs that can increase the long-distance and rigidity of the binder are used, and the conductive material that meets the above-mentioned composition is used to increase the ratio of active material in the negative electrode composition and increase the solid content of the negative electrode slurry, which is characterized by the ability to improve the performance of the cell itself.
[0018] In addition, in order to ensure the conductive network as described above and to prevent problems caused by the volume expansion of the silicon-based active material, a certain amount of binder is included based on the silicon-based active material.
[0019] That is, the negative electrode composition according to the present invention is mainly characterized in that, in a negative electrode in which a silicon-based active material is applied to maximize capacity, the ratio of the silicon-based active material contained therein is specified, and the part by weight of the negative electrode binder that can effectively suppress volume expansion and relaxation in accordance with the ratio, and the composition of the linear conductive material that can ensure a conductive network and suppress rigidity are optimized.
[0020] The main object of the present invention is to maintain the advantages of using a silicon-based active material when a negative electrode composition having the above-mentioned composition and content is applied to a negative electrode, while resolving problems such as a decrease in life characteristics and a break in the conductive network. [Brief description of the drawings]
[0021] [Figure 1] FIG. 1 is a diagram showing a laminated structure of a negative electrode for a lithium secondary battery according to an embodiment of the present application. [Diagram 2] FIG. 1 is a diagram showing a stacked structure of a lithium secondary battery according to an embodiment of the present application. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0022] Before describing the present invention, some terms will first be defined.
[0023] In this specification, when a part is said to "comprise" a certain component, this means that it may further include other components, not excluding other components, unless specifically stated to the contrary.
[0024] In this specification, "p to q" means a range of "not less than p and not more than q."
[0025] In this specification, the "specific surface area" is measured by the BET method, and specifically, is calculated from the amount of nitrogen gas adsorption at liquid nitrogen temperature (77K) using a BELSORP-mini II manufactured by BEL Japan Ltd. That is, in this application, the BET specific surface area may mean the specific surface area measured by the above-mentioned measurement method.
[0026] In this specification, "Dn" means particle size distribution, and refers to the particle size at the n% point of the cumulative particle number distribution according to the particle size. That is, D50 is the particle size (median particle size) at the 50% point of the cumulative particle number distribution according to the particle size, D90 is the particle size at the 90% point of the cumulative particle number distribution according to the particle size, and D10 is the particle size at the 10% point of the cumulative particle number distribution according to the particle size. Meanwhile, the median particle size can be measured using a laser diffraction method. Specifically, the powder to be measured is dispersed in a dispersion medium, and then introduced into a commercially available laser diffraction particle size measuring device (e.g., Microtrac S3500), and the difference in the diffraction pattern according to the size of the particles is measured when the particles pass through a laser beam to calculate the particle size distribution.
[0027] In one embodiment of the present application, the particle size or particle diameter may refer to the average diameter or representative diameter of individual grains that make up a particle.
[0028] In this specification, when a polymer contains a certain monomer as a monomer unit, it means that the monomer participates in a polymerization reaction and is included as a repeating unit in the polymer. In this specification, when it is said that a polymer contains a monomer, this is interpreted in the same way as the polymer containing the monomer as a monomer unit.
[0029] In this specification, unless otherwise specified as "homopolymer", the term "polymer" is understood to be used in a broad sense including copolymers.
[0030] In this specification, the weight average molecular weight (Mw) and the number average molecular weight (Mn) are the molecular weights in terms of polystyrene measured by Gel Permeation Chromatography (GPC) using various monodisperse polystyrene polymers (standard samples) of different degrees of polymerization commercially available for molecular weight measurement as standard substances. In this specification, unless otherwise specified, the molecular weight means the weight average molecular weight.
[0031] Hereinafter, with reference to the drawings, a detailed description will be given so that those having ordinary knowledge in the technical field to which the present invention pertains can easily implement the present invention. However, the present invention may be realized in various different forms and is not limited to the following description.
[0032] One embodiment of this specification provides a negative electrode composition containing a silicon-based active material; a linear conductive material; and a negative electrode binder, wherein the silicon-based active material includes one or more selected from the group consisting of SiOx (x = 0) and SiOx (0 < x < 2), contains 90 parts by weight or more of SiOx (x = 0) based on 100 parts by weight of the silicon-based active material, the linear conductive material includes SWCNT; and MWCNT, contains 80 parts by weight or more and 95 parts by weight or less of the silicon-based active material based on 100 parts by weight of the negative electrode composition, and contains 3 parts by weight or more and 10 parts by weight or less of the negative electrode binder based on 100 parts by weight of the silicon-based active material.
[0033] In the case of the negative electrode composition according to the present application, in a negative electrode applying a silicon-based active material to maximize the capacity, the ratio of the silicon-based active material contained is specified, and the weight part of the negative electrode binder capable of effectively suppressing the volume expansion and relaxation according to the ratio, and the composition of the linear conductive material capable of ensuring the conductivity network and suppressing the rigidity are optimized, which is the main feature.
[0034] Hereinafter, the negative electrode composition according to the present application will be described in detail.
[0035] In one embodiment of the present application, the silicon-based active material includes one or more selected from the group consisting of SiOx (x = 0) and SiOx (0 <x <2), and based on 100 parts by weight of the silicon-based active material, the SiOx (x = 0) may be included in an amount of 90 parts by weight or more.
[0036] In another embodiment, based on 100 parts by weight of the silicon-based active material, the SiOx (x = 0) may be included in an amount of 90 parts by weight or more, preferably 92 parts by weight or more, more preferably 93 parts by weight or more, and may be included in an amount of 100 parts by weight or less, preferably 99 parts by weight or less, more preferably 95 parts by weight or less.
[0037] In one embodiment of the present application, the silicon-based active material may be SiOx (x = 0).
[0038] In one embodiment of the present application, the silicon-based active material may be particularly pure silicon (Si) used as the silicon-based active material. Using pure silicon (Si) as the silicon-based active material means that, as described above, when based on 100 parts by weight of the entire silicon-based active material, it may mean including pure Si particles (SiOx (x = 0)) not bonded to other particles or elements within the above range.
[0039] In one embodiment of the present application, the crystal grain size of the silicon-based active material may be 200 nm or less.
[0040] In another embodiment, the crystal grain size of the silicon-based active material may be 200 nm or less, preferably 130 nm or less, more preferably 110 nm or less, even more preferably 100 nm or less, specifically 95 nm or less, more specifically 91 nm or less. The crystal grain size of the silicon-based active material may be in the range of 10 nm or more, preferably 15 nm or more.
[0041] The silicon-based active material has the above-mentioned grain size, and the grain size of the silicon-based active material can be adjusted by changing the process conditions in the manufacturing process. In this case, by satisfying the above-mentioned range, the grain boundaries are widely distributed, and lithium ions are uniformly inserted during lithium ion insertion, and the stress applied during lithium ion insertion into silicon particles can be reduced, thereby alleviating particle cracking. As a result, the negative electrode has the characteristic of improving its life stability. If the grain size exceeds the above-mentioned range, the grain boundaries within the particles are narrowly distributed, in which case lithium ions are non-uniformly inserted into the particles, and the stress due to ion insertion is large, resulting in particle cracking.
[0042] In one embodiment of the present application, the silicon-based active material may include a crystalline structure having a crystal grain distribution of 1 nm or more and 200 nm or less, and an area ratio of the crystalline structure may be 5% or less based on the total area of the silicon-based active material.
[0043] In another embodiment, the area ratio of the crystalline structure may be 5% or less, 3% or less, or 0.1% or more, based on the total area of the silicon-based active material.
[0044] That is, the silicon-based active material according to the present application has a crystal grain size of 200 nm or less, and the size of each crystal structure is small, so that the above-mentioned area ratio can be satisfied, and thus the distribution of the grain boundaries can be broadened, thereby providing the above-mentioned effects.
[0045] In one embodiment of the present application, the silicon-based active material may contain 20 or more crystal structures.
[0046] In another embodiment, the number of crystalline structures contained in the silicon-based active material may be 20 or more, 30 or more, 35 or more, and may be in the range of 60 or less, 50 or less.
[0047] That is, as described above, when the crystal grain size of the silicon-based active material satisfies the above range and the number of crystal structures satisfies the above range, the strength of the silicon-based active material itself has an appropriate range, and when contained in an electrode, flexibility can be imparted and volume expansion can be efficiently suppressed.
[0048] In this application, the term "crystal grain" refers to a crystal grain in a metal or material that is an aggregate of microscopic irregular shapes, and the term "crystal grain size" may refer to the diameter of the observed crystal grain. That is, in this application, the term "crystal grain size" refers to the size of a domain that shares the same crystal orientation within a grain, and has a different concept from the grain size or particle size that represents the size of a substance.
[0049] In one embodiment of the present application, the crystal grain size can be calculated from the FWHM (Full Width at Half Maximum) value by XRD analysis. The remaining values except L are measured by XRD analysis of the silicon-based active material, and the crystal grain size can be measured since the FWHM and the crystal grain size are inversely proportional to each other according to the Debye-Scherrer equation. In this case, the Debye-Scherrer equation is as shown in the following equation 1-1.
[0050] [Formula 1-1] FWHM=Kλ / LCosθ
[0051] In the above formula 1-1, L is the crystal grain size, K is a constant, θ is the Bragg angle, and λ is the wavelength of X-ray.
[0052] Furthermore, the crystal grains have various shapes and can be measured three-dimensionally. Generally, the crystal grain size can be measured by commonly used circle method and diameter measurement method, but is not limited thereto.
[0053] The diameter measurement method can be performed by drawing 5 to 10 equilibrium lines, each with a length of L mm, on a micrograph of the target particle, counting the number of crystal grains z on the lines, and averaging them. In this case, only those that fit completely are counted and excluded. If the number of lines is P and the magnification is V, the average grain size can be calculated by the following formula 1-2.
[0054] [Formula 1-2] Dm = (L*P*10 3 ) / (zV)(μm)
[0055] The circle method is a method in which a circle of a specified diameter is drawn on a micrograph of a target particle, and then the average area of the crystal grains is calculated based on the number of crystal grains that fall within the circle and the number of crystal grains that cross the boundary line, and can be calculated using the following formula 1-3.
[0056] [Formula 1-3] Fm = (Fk * 10 6 ) / ((0.67n+z)V 2 )(μm 2 )
[0057] In the above formula 1-3, Fm is the average particle area, Fk is the measured area on the photograph, z is the number of particles that fit within a circle, n is the number of particles that span an arc, and V is the magnification of the microscope.
[0058] In one embodiment of the present application, the silicon-based active material has a surface area of 0.25 m 2 / g or more.
[0059] In another embodiment, the silicon-based active material has a surface area of 0.25 m 2 / g or more, preferably 0.28m 2 / g or more, more preferably 0.30m 2 / g or more, specifically 0.31m 2 / g or more, more specifically 0.32m 2 The silicon-based active material may have a surface area of 3 m 2 / g or less, preferably 2.5m 2 / g or less, more preferably 2.2m 2 The surface area can be measured according to DIN 66131 (with nitrogen).
[0060] The silicon-based active material has the above surface area, and the size of the surface area of the silicon-based active material can be adjusted by changing the process conditions in the manufacturing process and the growth conditions of the silicon-based active material. That is, when the silicon-based active material is manufactured by the manufacturing method of the present application, it has a larger surface area than particles having the same particle size due to the rough surface, and in this case, it has the characteristic that the cracks in the electrode caused by repeated charge and discharge cycles can be mitigated by satisfying the above range and increasing the binding force with the binder.
[0061] In addition, lithium ions are uniformly inserted during lithium ion insertion, so that the stress applied during lithium ion insertion into silicon particles can be reduced, thereby alleviating particle cracking. As a result, the negative electrode has the characteristic of improving its life stability. If the surface area is less than the above range, even if the particle size is the same, the surface is formed smoothly, and the binding force with the binder is reduced, causing cracks in the electrode. In this case, lithium ions are non-uniformly inserted into the particles, and the stress due to ion insertion is large, causing particle cracking.
[0062] In one embodiment of the present application, the silicon-based active material satisfies the range of the following formula 2-1.
[0063] [Formula 2-1] X1 / Y1≦0.960
[0064] In the above formula 2-1, X1 is the actual area of the silicon-based active material, Y1 means the area of a spherical particle of the silicon-based active material having the same perimeter.
[0065] The formula 2-1 can be measured using a granular analyzer. Specifically, the silicon-based active material according to the present application is scattered onto a glass plate by air injection, and then a shadow image of the scattered silicon-based active material particles is taken, and the shapes of 10,000 silicon-based active material particles in the image are measured. In this case, the formula 2-1 is a value representing the average for 10,000 particles. The formula 2-1 according to the present application can be measured from the image, and the formula 2-1 can be expressed as the sphericity of the silicon-based active material. The sphericity can be calculated according to the formula [4π*actual area of silicon-based active material / (boundary) 2 ] may also be expressed as
[0066] In one embodiment of the present application, the sphericity of the silicon-based active material may be, for example, 0.960 or less, for example, 0.957 or less. The sphericity of the silicon-based active material may be 0.8 or more, for example, 0.9 or more, specifically 0.93 or more, more specifically 0.94 or more, for example, 0.941 or more.
[0067] In one embodiment of the present application, the silicon-based active material satisfies the range of the following formula 2-2.
[0068] [Formula 2-2] X2 / Y2≦0.995
[0069] In the above formula 2-2, Y2 is the actual perimeter of the silicon-based active material, X2 is the perimeter of the circumscribing figure of the silicon-based active material.
[0070] The formula 2-2 can be measured using a granular analyzer. Specifically, the silicon-based active material according to the present application is scattered on a glass plate by air injection, and then the scattered silicon-based active material particles are photographed as a shadow image, and the shapes of 10,000 silicon-based active material particles in the photograph are measured. In this case, the formula 2-2 is a value representing the average for 10,000 particles. The formula 2-2 according to the present application can be measured from the image, and the formula 2-2 can be expressed as the convexity of the silicon-based active material.
[0071] In one embodiment of the present application, the range of X2 / Y2≦0.996, preferably X2 / Y2≦0.995, may be satisfied, or the range of 0.8≦X2 / Y2, preferably 0.9≦X2 / Y2, more preferably 0.95≦X2 / Y2, specifically 0.98≦X2 / Y2 may be satisfied.
[0072] The smaller the value of the formula 2-1 or 2-2, the greater the roughness of the silicon-based active material. When a silicon-based active material having the above range is used, the bonding strength with the binder is increased, thereby providing the characteristic that cracks in the electrode caused by repeated charge / discharge cycles can be alleviated.
[0073] In one embodiment of the present application, the silicon-based active material may include silicon-based particles having a particle size distribution of 0.01 μm or more and 30 μm or less.
[0074] The silicon-based active material containing silicon-based particles having a particle size distribution of 0.01 μm or more and 30 μm or less means that the material contains a plurality of individual silicon-based particles having a particle size within the above range, and the number of silicon-based particles contained is not limited.
[0075] The particle size of the silicon-based particles may be expressed as a diameter when the particles are spherical, but when the particles are not spherical but have other shapes, the particle size can be measured in comparison with the spherical shape, and the particle size of each silicon-based particle can be measured by a method generally used in the art.
[0076] On the other hand, the average particle size (D50) of the silicon-based active material of the present invention may be 5 μm to 10 μm, specifically 5.5 μm to 8 μm, and more specifically 6 μm to 7 μm. When the average particle size is within the above range, the specific surface area of the particles is within a suitable range, and the viscosity of the negative electrode slurry is formed within a suitable range. This allows smooth dispersion of the particles constituting the negative electrode slurry. In addition, when the size of the silicon-based active material is equal to or greater than the above lower limit range, the contact area between the silicon particles and the conductive material is excellent due to the composite of the conductive material and the binder in the negative electrode slurry, and the conductive network is more likely to be maintained, thereby increasing the capacity retention rate. On the other hand, when the average particle size satisfies the above range, excessively large silicon particles are excluded, and the surface of the negative electrode is formed smoothly, thereby preventing the non-uniformity of the current density during charging and discharging.
[0077] In one embodiment of the present application, the silicon-based active material generally has a characteristic BET specific surface area. The BET specific surface area of the silicon-based active material is preferably less than 0.01 m 2 / g~150.0m 2 / g, more preferably 0.1m 2 / g~100.0m 2 / g, particularly preferably 0.2m 2 / g~80.0m 2 / g, most preferably 0.2m 2 / g~18.0m 2 / g. The BET specific surface area is determined in accordance with DIN 66131 (with nitrogen).
[0078] In one embodiment of the present application, silicon-based active material may be, for example, in crystalline or amorphous form, and is preferably non-porous.Silicon particles are preferably spherical or shard particles.Alternatively, but less advantageously, silicon particles may also have a fibrous structure or be in the form of silicon-containing film or coating.
[0079] In one embodiment of the present application, the silicon-based active material may be included in an amount of 80 parts by weight or more and 95 parts by weight or less based on 100 parts by weight of the negative electrode composition.
[0080] In another embodiment, the silicon-based active material may be included in an amount of 80 parts by weight or more, preferably 83 parts by weight or more, more preferably 85 parts by weight or more, based on 100 parts by weight of the negative electrode composition, and may be included in an amount of 95 parts by weight or less, preferably 93 parts by weight or less, more preferably 91 parts by weight or less.
[0081] The negative electrode composition according to the present application uses a silicon-based active material with a remarkably high capacity within the above range. That is, when the amount exceeds the above range, the life characteristics cannot be ensured even when the combination of the linear conductive material and the binder of the present invention is used, and the cell performance evaluation is rather poor. When the amount is less than the above range, the life characteristics can be ensured, but the capacity characteristics and energy density are significantly reduced, and when a negative electrode having the same capacity is manufactured, the thickness of the active material layer increases and the quick charging performance is also deteriorated.
[0082] The present application uses a silicon-based active material in the above range that can control the volume expansion and maximize the capacity characteristics, and is characterized by optimizing the contents of the linear conductive material and binder described below.
[0083] The battery contains a certain amount of a specific carbon-based material that can suppress the volume expansion rate during charging and discharging and does not cause any problems with capacity characteristics, resulting in high capacity characteristics and improved electrode life characteristics.
[0084] In one embodiment of the present application, the silicon-based active material may have a non-spherical shape, and the sphericity is, for example, 0.9 or less, for example, 0.7 to 0.9, for example, 0.8 to 0.9, for example, 0.85 to 0.9.
[0085] In this application, the circularity is determined by the following formula 1, where A is the area and P is the perimeter.
[0086] [Formula 1] 4πA / P 2
[0087] In the past, it was common to use only graphite-based compounds as negative electrode active materials, but in recent years, as the demand for high-capacity batteries has increased, attempts to mix and use silicon-based active materials to increase capacity have been increasing. However, in the case of silicon-based active materials, even if the properties of the silicon-based active materials themselves are partially adjusted as described above, the volume of the silicon-based active materials rapidly expands during charging / discharging, which may cause some problems in that the conductive path formed in the negative electrode active material layer is damaged.
[0088] Therefore, in one embodiment of the present application, the negative electrode conductive material includes a linear conductive material, and the linear conductive material may include SWCNTs and MWCNTs.
[0089] Generally, conventional silicon-based negative electrodes may include both dot-shaped conductive materials and sheet-shaped conductive materials. However, the conductive material of the present application includes only linear conductive materials, and the linear conductive materials include SWCNTs and MWCNTs.
[0090] The dot-shaped conductive material can be used to improve the conductivity of the negative electrode, does not cause chemical changes, and has conductivity, and refers to a spherical or dot-shaped conductive material. Specifically, the dot-shaped conductive material may be at least one selected from the group consisting of natural graphite, artificial graphite, carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, conductive fiber, fluorocarbon, aluminum powder, nickel powder, zinc oxide, potassium titanate, titanium oxide, and polyphenylene derivatives, and preferably includes carbon black in terms of realizing high conductivity and excellent dispersibility.
[0091] The sheet-like conductive material can increase surface contact between silicon particles in the negative electrode to improve conductivity and suppress disconnection of the conductive path due to volume expansion, and can be referred to as a plate-like conductive material or a bulk-like conductive material. The sheet-like conductive material may include at least one selected from the group consisting of plate-like graphite, graphene, graphene oxide, and graphite flakes, and may be preferably plate-like graphite.
[0092] First, when carbon black is used as a dot-like conductive material in a silicon-based negative electrode, it has the advantage of being inexpensive in terms of processing cost, but in order to fulfill its role, it must be included in the negative electrode composition at a high ratio. Since it is necessary to use such a high ratio of dot-like conductive material, gas generation at high temperatures becomes an issue, and the gas generation causes a problem of a decrease in the stability of the negative electrode.
[0093] In addition, plate-shaped graphite used as a sheet-shaped conductive material has a reasonable price, suitable rigidity, and a soft form that acts as a buffer when rolling a silicon-based negative electrode, and has a high specific surface area, which allows the formation of a conductive network between active materials. However, since a sheet-shaped conductive material must be contained in a certain amount relative to the silicon-based active material used, there is a limit to the amount of silicon-based active material that can be contained in the negative electrode active material despite the above-mentioned properties, which causes a problem in which it is not possible to maximize the capacity characteristics.
[0094] Furthermore, there have been attempts to solve certain problems by appropriately combining the above-mentioned point-like conductive materials and sheet-like conductive materials, but the above-mentioned problems of point-like conductive materials and sheet-like conductive materials have still not been solved.
[0095] However, the negative electrode conductive material according to the present application is characterized in that it contains only linear conductive materials, and in particular that the linear conductive materials contain SWCNTs and MWCNTs.
[0096] In the present application, the SWCNTs have a specific surface area of 900 m2 / g~1500m 2 / g and the mean diameter may be 50 nm or more and 450 nm or less.
[0097] In one embodiment of the present application, the SWCNTs may have a mean diameter of 50 nm or more and 450 nm or less, a length of 5 μm or more and 20 μm or less, and an average aspect ratio of 15 to 100.
[0098] The SWCNTs are long and have a high specific surface area, and are the most effective for forming a conductive network between silicon-based active materials. However, SWCNTs have the disadvantage of being very expensive, and when the SWCNTs are used in excess, the stiffness is reduced because the SWCNT dispersant used in combination is also included.
[0099] In the present application, the MWCNTs have a specific surface area of 100 m 2 / g~500m 2 / g and the mean diameter may be 10 nm or more and 20 nm or less.
[0100] In the present application, the MWCNTs may have a mean diameter of 10 nm or more and 20 nm or less, a length of 300 nm or more and 1000 nm or less, and an average aspect ratio of 15-100.
[0101] The MWCNT has a smaller specific surface area and is inferior in length to the SWCNT, as described above, but is a material that has much better performance than the dot-like conductive material and sheet-like conductive material described above.
[0102] In this application, SWCNTs have a high specific surface area and a large aspect ratio, and MWCNTs are used in a bundled form and are located on the surface of the silicon-based active material, making it difficult to connect the active materials together, i.e., SWCNTs are used for long-distance connection, and MWCNTs are used for mixing with the particle surface and binder composite.
[0103] In one embodiment of the present application, there is provided a negative electrode composition, in which the linear conductive material is contained in an amount of 0.5 parts by weight or more and 10 parts by weight or less, based on 100 parts by weight of the silicon-based active material.
[0104] In another embodiment, the linear conductive material may be included in an amount of 0.5 parts by weight or more and 10 parts by weight or less, preferably 0.6 parts by weight or more and 8 parts by weight or less, and more preferably 0.6 parts by weight or more and 7 parts by weight or less, based on 100 parts by weight of the silicon-based active material.
[0105] In one embodiment of the present application, the negative electrode conductive material includes a linear conductive material and satisfies the above-mentioned composition and ratio, so that the battery has the characteristics of having many points at which charging and discharging are possible and excellent output characteristics at a high C-rate without significantly affecting the life characteristics of conventional lithium secondary batteries.
[0106] In one embodiment of the present application, the MWCNT may be 0.3 parts by weight or more and 6 parts by weight or less, and the SWCNT may be 0.1 parts by weight or more and 1.5 parts by weight or less, based on 100 parts by weight of the silicon-based active material.
[0107] In another embodiment, the MWCNT may be 0.3 parts by weight or more and 6 parts by weight or less, preferably 1.0 parts by weight or more and 5.5 parts by weight or less, and more preferably 2.0 parts by weight or more and 3.5 parts by weight or less, based on 100 parts by weight of the silicon-based active material.
[0108] In another embodiment, the SWCNTs may be present in an amount of 0.3 parts by weight or more and 1.5 parts by weight or less, preferably 0.5 parts by weight or more and 1.0 parts by weight or less, based on 100 parts by weight of the silicon-based active material.
[0109] That is, in the case of the linear conductive material according to the present application, SWCNT is not used alone, but MWCNT, which is an inferior material to SWCNT, is also included in the conductive network in the above weight parts in order to solve the above-mentioned problems of cost and rigidity. That is, by adjusting the weight parts of the linear conductive material as described above and adjusting the ratios of SWCNT and MWCNT therein, it has been confirmed through research that it is cost-effective and can achieve effects equal to or superior to those when SWCNT is used alone.
[0110] As a result, compared to the case where dot-like and sheet-like conductive materials, including linear conductive materials, can be used, the silicon-based negative electrode active material can be contained in a high content, so that good capacity characteristics can be formed. In addition, by using the above-mentioned combination of linear conductive materials, a conductive network can be secured even with a certain amount of volume expansion, and further, by adjusting the negative electrode binder described later, the volume expansion can also be solved.
[0111] The negative electrode conductive material according to the present application has a completely different structure from the positive electrode conductive material applied to the positive electrode. That is, the negative electrode conductive material according to the present application serves to form a contact between silicon-based active materials, which have a very large volume expansion of the electrodes due to charging and discharging, while the positive electrode conductive material serves as a buffer during rolling and also serves to impart some electrical conductivity, and thus has a completely different structure and role from the negative electrode conductive material of the present invention.
[0112] In addition, the negative electrode conductive material according to the present application is applied to a silicon-based active material, and has a completely different structure from a conductive material applied to a graphite-based active material. That is, a conductive material used in an electrode having a graphite-based active material has particles that are simply smaller than the active material, and therefore has the properties of improving output characteristics and imparting some electrical conductivity, and has a completely different structure and role from a negative electrode conductive material applied together with a silicon-based active material as in the present invention.
[0113] In one embodiment of the present application, there is provided a negative electrode composition, wherein the negative electrode binder includes one or more selected from the group consisting of a rubber-based binder and a water-based binder.
[0114] In one embodiment of the present application, the negative electrode binder may include at least one selected from the group consisting of polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinylidene fluoride, polyacrylonitrile, polymethylmethacrylate, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, polyacrylic acid, ethylene-propylene-diene monomer (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber, polyacrylic acid, and substances in which hydrogen is substituted with Li, Na, Ca, or the like, or may include various copolymers thereof.
[0115] The negative electrode binder according to one embodiment of the present application plays a role of holding the active material and the conductive material in order to prevent distortion and structural deformation of the negative electrode structure when the volume of the silicon-based active material expands and relaxes. As long as the above-mentioned role is fulfilled, any common binder can be applied, and specifically, a water-based binder may be used, and more specifically, a PAM-based binder may be used.
[0116] In one embodiment of the present application, there is provided a negative electrode for a lithium secondary battery, wherein the negative electrode binder includes a water-based binder, and the negative electrode binder is 5 parts by weight or more and 15 parts by weight or less based on 100 parts by weight of the negative electrode composition.
[0117] In another embodiment, the negative electrode binder may be 5 parts by weight or more and 15 parts by weight or less, preferably 7 parts by weight or more and 13 parts by weight or less, and more preferably 9 parts by weight or more and 12 parts by weight or less, based on 100 parts by weight of the negative electrode composition.
[0118] In one embodiment of the present application, the negative electrode binder may be included in an amount of 3 parts by weight or more and 10 parts by weight or less based on 100 parts by weight of the silicon-based active material.
[0119] In another embodiment, the negative electrode binder may be 3 parts by weight or more and 10 parts by weight or less, preferably 3.5 parts by weight or more and 9.5 parts by weight or less, and more preferably 4 parts by weight or more and 9 parts by weight or less, based on 100 parts by weight of the silicon-based active material.
[0120] In the case of the negative electrode for a lithium secondary battery according to the present application, the silicon-based active material is used in the above weight parts in order to maximize the capacity characteristics, and the volume expansion during charging and discharging is larger than that in the case of using a conventional carbon-based active material as the main active material. Therefore, by including the above weight parts of the negative electrode binder, the volume expansion of the silicon-based active material, which has high rigidity, due to charging and discharging can be efficiently suppressed.
[0121] In one embodiment of the present application, there is provided a negative electrode for a lithium secondary battery, comprising: a negative electrode current collector layer; and a negative electrode active material layer formed on one or both sides of the negative electrode current collector layer, the negative electrode active material layer comprising the negative electrode composition according to the present application.
[0122] 1 is a diagram showing a laminated structure of a negative electrode for a lithium secondary battery according to an embodiment of the present application. Specifically, a negative electrode for a lithium secondary battery 100 including a negative electrode active material layer 20 on one side of a negative electrode current collector layer 10 can be seen. Although FIG. 1 shows a negative electrode active material layer formed on one side, the layer may be formed on both sides of the negative electrode current collector layer.
[0123] In one embodiment of the present application, the negative electrode for a lithium secondary battery may be formed by applying a negative electrode slurry containing the negative electrode composition to one or both surfaces of a negative electrode current collector layer, and drying the applied slurry.
[0124] In this case, the negative electrode slurry may include the above-mentioned negative electrode composition and a slurry solvent.
[0125] In one embodiment of the present application, the solid content of the negative electrode slurry may be 5% or more and 55% or less.
[0126] In another embodiment, the solid content of the negative electrode slurry may satisfy the range of 5% to 55%, preferably 7% to 35%, and more preferably 10% to 30%.
[0127] The solid content of the negative electrode slurry refers to the content of the negative electrode composition contained in the negative electrode slurry, and may refer to the content of the negative electrode composition based on 100 parts by weight of the negative electrode slurry.
[0128] When the solid content of the negative electrode slurry satisfies the above range, the viscosity during the formation of the negative electrode active material layer is suitable, and the particle aggregation phenomenon of the negative electrode composition is minimized, so that the negative electrode active material layer can be efficiently formed. In addition, the negative electrode composition according to the present application includes a linear conductive material and a high content of a silicon-based active material, and is characterized by excellent fast charging performance and cell performance.
[0129] In one embodiment of the present application, the slurry solvent can be used without limitation as long as it can dissolve the negative electrode composition. Specifically, water, acetone, or NMP may be used.
[0130] In one embodiment of the present application, the negative electrode current collector layer generally has a thickness of 1 μm to 100 μm. Such a negative electrode current collector layer is not particularly limited as long as it does not cause a chemical change in the battery and has high conductivity, and for example, copper, stainless steel, aluminum, nickel, titanium, baked carbon, copper or stainless steel surface-treated with carbon, nickel, titanium, silver, etc., aluminum-cadmium alloy, etc. may be used. In addition, fine irregularities may be formed on the surface to strengthen the binding force of the negative electrode active material, and it may be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.
[0131] In one embodiment of the present application, there is provided a negative electrode for a lithium secondary battery, wherein the negative electrode current collector layer has a thickness of 1 μm or more and 100 μm or less, and the negative electrode active material layer has a thickness of 10 μm or more and 500 μm or less.
[0132] In the present application, the thickness of the negative electrode active material layer may refer to the thickness of a single layer of the negative electrode active material layer when the layer is formed on one surface of the negative electrode current collector layer.
[0133] However, the thickness may vary depending on the type and application of the negative electrode used, and is not limited thereto.
[0134] In one embodiment of the present application, the porosity of the negative electrode active material layer may be in the range of 10% or more and 60% or less.
[0135] In another embodiment, the porosity of the negative electrode active material layer may be in the range of 10% or more and 60% or less, preferably 20% or more and 50% or less, and more preferably 30% or more and 45% or less.
[0136] The porosity varies depending on the composition and content of the silicon-based active material, conductive material, and binder contained in the negative electrode active material layer, and in particular, the silicon-based active material and conductive material according to the present application are contained in a specific composition and content, thereby satisfying the above range, and the electrode is characterized by having an appropriate range of electrical conductivity and resistance.
[0137] In one embodiment of the present application, there is provided a lithium secondary battery comprising: a positive electrode; a negative electrode for a lithium secondary battery according to the present application; a separator provided between the positive electrode and the negative electrode; and an electrolyte.
[0138] 2 is a diagram showing a laminated structure of a lithium secondary battery according to an embodiment of the present application. Specifically, a negative electrode 100 for a lithium secondary battery including a negative electrode active material layer 20 on one side of a negative electrode current collector layer 10 can be seen, and a positive electrode 200 for a lithium secondary battery including a positive electrode active material layer 40 on one side of a positive electrode current collector layer 50 can be seen, and the negative electrode 100 for a lithium secondary battery and the positive electrode 200 for a lithium secondary battery are formed into a laminated structure with a separator 30 interposed therebetween.
[0139] A secondary battery according to an embodiment of the present specification may include the negative electrode for a lithium secondary battery described above. Specifically, the secondary battery may include a negative electrode, a positive electrode, a separator interposed between the positive electrode and the negative electrode, and an electrolyte, and the negative electrode is the same as the negative electrode described above. The negative electrode has been described above, so a detailed description thereof will be omitted.
[0140] The positive electrode may include a positive electrode current collector, and a positive electrode active material layer formed on the positive electrode current collector and including the positive electrode active material.
[0141] In the positive electrode, the positive electrode current collector is not particularly limited as long as it does not cause a chemical change in the battery and has conductivity, and for example, stainless steel, aluminum, nickel, titanium, baked carbon, or aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, etc. may be used. The positive electrode current collector may usually have a thickness of 3 μm to 500 μm, and fine irregularities may be formed on the surface of the current collector to increase the adhesive force of the positive electrode active material. For example, it may be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.
[0142] The positive electrode active material may be a commonly used positive electrode active material. Specifically, the positive electrode active material may be a layered compound such as lithium cobalt oxide (LiCoO2) or lithium nickel oxide (LiNiO2) or a compound substituted with one or more transition metals; a lithium iron oxide such as LiFe3O4; 1+c1 Mn 2-c1 O4 (0≦c1≦0.33), lithium manganese oxides such as LiMnO3, LiMn2O3, LiMnO2; lithium copper oxide (Li2CuO2); vanadium oxides such as LiV3O8, V2O5, Cu2V2O7; chemical formula LiNi 1-c2 Ni-site type lithium nickel oxide represented by the chemical formula LiMn 2-c3 M c3 Examples of the lithium manganese composite oxide include, but are not limited to, lithium manganese oxide represented by Li2Mn3MO8 (wherein M is at least one selected from the group consisting of Co, Ni, Fe, Cr, Zn, and Ta, and satisfies 0.01≦c3≦0.6) or Li2Mn3MO8 (wherein M is at least one selected from the group consisting of Fe, Co, Ni, Cu, and Zn); and LiMn2O4 in which part of the Li in the chemical formula is replaced with an alkaline earth metal ion. The positive electrode may be Li metal.
[0143] In one embodiment of the present application, the positive electrode active material includes a lithium transition metal composite compound including nickel (Ni), cobalt (Co), and manganese (Mn), and the lithium transition metal composite compound includes single particles or secondary particles, and the average particle size (D50) of the single particles may be 1 μm or more.
[0144] For example, the average particle size (D50) of the single particles may be 1 μm or more and 12 μm or less, 1 μm or more and 8 μm or less, 1 μm or more and 6 μm or less, more than 1 μm and 12 μm or less, more than 1 μm and 8 μm or less, or more than 1 μm and 6 μm or less.
[0145] The single particle can have excellent particle strength even if it is formed to have a small particle size (D50) of 1 μm or more and 12 μm or less. For example, the single particle has a strength of 650 kgf / cm 2 The particle strength may be 100 to 300 MPa when the particle is rolled with a force of 650 kgf / cm. 2 Even if the electrode is rolled with a strong force, the phenomenon of an increase in fine particles in the electrode due to particle cracking is mitigated, thereby improving the life characteristics of the battery.
[0146] The single particles can be produced by mixing a transition metal precursor and a lithium source material and sintering the mixture. The secondary particles can be produced by a method different from that of the single particles, and the composition of the secondary particles can be the same as or different from that of the single particles.
[0147] The method for forming the single particles is not particularly limited, but may generally be formed by over-firing at an elevated firing temperature, using additives such as grain growth promoters that aid in over-firing, or by changing the starting material.
[0148] For example, the sintering is performed at a temperature at which single particles can be formed. In order to form the single particles, the sintering must be performed at a temperature higher than that at which the secondary particles are produced. For example, when the precursor composition is the same, the sintering must be performed at a temperature about 30°C to 100°C higher than that at which the secondary particles are produced. The sintering temperature for forming the single particles may vary depending on the metal composition in the precursor. For example, when a high-content nickel (High-Ni) NCM-based lithium transition metal composite oxide having a nickel (Ni) content of 80 mol% or more is to be formed into single particles, the sintering temperature may be about 700°C to 1000°C, preferably about 800°C to 950°C. When the sintering temperature satisfies the above range, a positive electrode active material including single particles having excellent electrochemical properties can be produced. When the sintering temperature is less than 790°C, a positive electrode active material including a lithium transition metal composite compound in the form of secondary particles is produced, and when the sintering temperature exceeds 950°C, the sintering is performed excessively, and the layered crystal structure is not properly formed, which may result in a decrease in electrochemical properties.
[0149] In this specification, the term "single particle" is used to distinguish it from conventional secondary particles formed by agglomeration of tens to hundreds of primary particles, and is a concept that includes a single particle consisting of one primary particle and a similar-single particle form that is an agglomeration of 30 or less primary particles.
[0150] Specifically, in the present invention, the single particle may be a single particle consisting of one primary particle or a quasi-single particle form that is an aggregate of 30 or less primary particles, and the secondary particle may be in the form of an aggregate of several hundred primary particles.
[0151] In one embodiment of the present application, the lithium transition metal composite compound that is the positive electrode active material further includes secondary particles, and the average particle size (D50) of the single particles is smaller than the average particle size (D50) of the secondary particles.
[0152] In the present invention, the single particle may be a single particle consisting of one primary particle or a quasi-single particle form that is an aggregate of 30 or less primary particles, and the secondary particle may be in the form of an aggregate of several hundred primary particles.
[0153] The lithium transition metal composite compound may further include secondary particles. The secondary particles refer to a form formed by agglomeration of primary particles, and can be distinguished from the concept of single particles including a similar-single particle form that is one primary particle, one single particle, or an agglomeration of 30 or less primary particles.
[0154] The particle diameter (D50) of the secondary particles may be 1 μm to 20 μm, 2 μm to 17 μm, and preferably 3 μm to 15 μm. The specific surface area (BET) of the secondary particles is 0.05 m 2 / g~10m 2 / g, preferably 0.1m 2 / g~1m 2 / g, more preferably 0.3m 2 / g~0.8m 2 / g.
[0155] In a further embodiment of the present application, the secondary particles are aggregates of primary particles, and the primary particles have an average particle size (D50) of 0.5 μm to 3 μm. Specifically, the secondary particles may be in the form of aggregates of several hundreds of primary particles, and the primary particles may have an average particle size (D50) of 0.6 μm to 2.8 μm, 0.8 μm to 2.5 μm, or 0.8 μm to 1.5 μm.
[0156] When the average particle size (D50) of the primary particles is within the above range, a single particle positive electrode active material having excellent electrochemical properties can be formed. If the average particle size (D50) of the primary particles is too small, the number of agglomerates of the primary particles forming the lithium nickel oxide particles increases, and the effect of suppressing particle cracking during rolling decreases. If the average particle size (D50) of the primary particles is too large, the lithium diffusion path inside the primary particles becomes long, increasing resistance and causing a decrease in output characteristics.
[0157] According to a further embodiment of the present application, the average particle size (D50) of the single particles is smaller than the average particle size (D50) of the secondary particles, so that the single particles can have excellent particle strength even when formed to have a small particle size, and thus the phenomenon of an increase in fine particles in the electrode due to particle cracking can be mitigated, thereby improving the life characteristics of the battery.
[0158] In one embodiment of the present application, the average particle size (D50) of the single particles is smaller than the average particle size (D50) of the secondary particles by 1 μm to 18 μm.
[0159] For example, the average particle size (D50) of the single particles may be 1 μm to 16 μm smaller, 1.5 μm to 15 μm smaller, or 2 μm to 14 μm smaller than the average particle size (D50) of the secondary particles.
[0160] When the average particle size (D50) of the single particles is smaller than the average particle size (D50) of the secondary particles, for example, when the above range is satisfied, the single particles can have excellent particle strength even if they are formed to have a small particle size, and thus the phenomenon of an increase in fine particles in the electrode due to particle cracking is mitigated, resulting in an improvement in the life characteristics and energy density of the battery.
[0161] According to a further embodiment of the present application, the single particles are contained in an amount of 15 parts by weight to 100 parts by weight relative to 100 parts by weight of the positive electrode active material. The single particles may be contained in an amount of 20 parts by weight to 100 parts by weight, or 30 parts by weight to 100 parts by weight relative to 100 parts by weight of the positive electrode active material.
[0162] For example, the single particles may be included in an amount of 15 parts by weight or more, 20 parts by weight or more, 25 parts by weight or more, 30 parts by weight or more, 35 parts by weight or more, 40 parts by weight or more, or 45 parts by weight or more, based on 100 parts by weight of the positive electrode active material. The single particles may be included in an amount of 100 parts by weight or less, based on 100 parts by weight of the positive electrode active material.
[0163] When the single particles are contained in the above range, excellent battery characteristics can be exhibited in combination with the above-mentioned negative electrode material. In particular, when the single particles are 15 parts by weight or more, the phenomenon of an increase in fine particles in the electrode due to particle cracking during rolling after the electrode preparation can be mitigated, thereby improving the life characteristics of the battery.
[0164] In one embodiment of the present application, the lithium composite transition metal compound may further include secondary particles, and the secondary particles may be 85 parts by weight or less relative to 100 parts by weight of the positive electrode active material. The secondary particles may be 80 parts by weight or less, 75 parts by weight or less, or 70 parts by weight or less relative to 100 parts by weight of the positive electrode active material. The secondary particles may be 0 parts by weight or more relative to 100 parts by weight of the positive electrode active material.
[0165] When the above range is satisfied, the above-mentioned effect due to the presence of the single particle positive electrode active material can be maximized. When the secondary particle positive electrode active material is included, the component may be the same as or different from the components exemplified as the single particle positive electrode active material described above, and may refer to an aggregated form of single particles.
[0166] In one embodiment of the present application, the positive electrode active material may be contained in an amount of 80 parts by weight or more and 99.9 parts by weight or less, preferably 90 parts by weight or more and 99.9 parts by weight or less, more preferably 95 parts by weight or more and 99.9 parts by weight or less, and even more preferably 98 parts by weight or more and 99.9 parts by weight or less, relative to 100 parts by weight of the positive electrode active material layer.
[0167] The positive electrode active material layer may contain a positive electrode conductive material and a positive electrode binder in addition to the positive electrode active material described above.
[0168] In this case, the positive electrode conductive material is used to impart conductivity to the electrode, and can be used without any particular limitation as long as it has electronic conductivity without causing chemical changes in the battery that is constructed.Specific examples include graphite such as natural graphite and artificial graphite; carbon-based materials such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, and carbon fibers; metal powders or metal fibers such as copper, nickel, aluminum, and silver; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and conductive polymers such as polyphenylene derivatives, and the like, and one or more of these may be used alone or in mixture.
[0169] The positive electrode binder plays a role of improving the adhesion between the positive electrode active material particles and the adhesive strength between the positive electrode active material and the positive electrode current collector.Specific examples include polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated-EPDM, styrene-butadiene rubber (SBR), fluororubber, and various copolymers thereof, and one or more of these may be used alone or in combination.
[0170] The separator separates the negative electrode and the positive electrode and provides a path for lithium ions to move. Any separator that is generally used as a separator in a secondary battery can be used without any particular limitation. In particular, it is preferable that the separator has low resistance to ion movement of the electrolyte and has excellent electrolyte moisture absorption ability. Specifically, a porous polymer film, for example, a porous polymer film made of a polyolefin polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, and an ethylene / methacrylate copolymer, or a laminate structure of two or more layers thereof may be used. In addition, a normal porous nonwoven fabric, for example, a nonwoven fabric made of high-melting point glass fiber, polyethylene terephthalate fiber, etc. may be used. In addition, in order to ensure heat resistance or mechanical strength, a separator coated with a ceramic component or a polymeric substance may be used, and may be selectively used as a single layer or multilayer structure.
[0171] Examples of the electrolyte include, but are not limited to, organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel-type polymer electrolytes, solid inorganic electrolytes, and molten inorganic electrolytes that can be used in the manufacture of lithium secondary batteries.
[0172] Specifically, the electrolyte may include a non-aqueous organic solvent and a metal salt.
[0173] Examples of the non-aqueous organic solvent that can be used include aprotic organic solvents such as N-methyl-2-pyrrolidinone, propylene carbonate, ethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, γ-butyrolactone, 1,2-dimethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, dimethyl sulfoxide, 1,3-dioxolane, formamide, dimethylformamide, dioxolane, acetonitrile, nitromethane, methyl formate, methyl acetate, phosphoric acid triester, trimethoxymethane, dioxolane derivatives, sulfolane, methylsulfolane, 1,3-dimethyl-2-imidazolidinone, propylene carbonate derivatives, tetrahydrofuran derivatives, ethers, methyl propionate, and ethyl propionate.
[0174] In particular, ethylene carbonate and propylene carbonate, which are cyclic carbonates among the carbonate-based organic solvents, can be preferably used as high-viscosity organic solvents, because they have a high dielectric constant and dissociate lithium salts well. When such cyclic carbonates are mixed in an appropriate ratio with linear carbonates having low viscosity and low dielectric constant, such as dimethyl carbonate and diethyl carbonate, an electrolyte having high electrical conductivity can be prepared, and therefore such a mixture can be used even more preferably.
[0175] As the metal salt, a lithium salt may be used. The lithium salt is a substance that is easily dissolved in the non-aqueous electrolyte. For example, the anion of the lithium salt is F - , Cl - , I - , NO3 - , N(CN)2 - , BF4 - , ClO4 - , PF6 - , (CF3)2PF4 - , (CF3)3PF3 - , (CF3)4PF2 - , (CF3)5PF - , (CF3)6P - , CF3SO3 - , CF3CF2SO3- , (CF3SO2)2N - , (FSO2)2N - , CF3CF2(CF3)2CO - , (CF3SO2)2CH - , (SF5)3C - , (CF3SO2)3C - , CF3(CF2)7SO3 - , CF3CO2 - , CH3CO2 - , SCN - , and (CF3CF2SO2)2N - One or more selected from the group consisting of may be used.
[0176] In addition to the constituent components of the electrolyte, the electrolyte may further include one or more additives such as a haloalkylene carbonate compound such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ether, ethylenediamine, n-glyme, hexaphosphoric acid triamide, nitrobenzene derivatives, sulfur, quinoneimine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidines, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol, or aluminum trichloride, for the purpose of improving the life characteristics of the battery, suppressing a decrease in battery capacity, and improving the discharge capacity of the battery.
[0177] According to an embodiment of the present invention, there is provided a battery module including the secondary battery as a unit cell, and a battery pack including the battery module. The battery module and the battery pack include the secondary battery having high capacity, high rate characteristics, and high cycle characteristics, and therefore can be used as a power source for a medium- to large-sized device selected from the group consisting of an electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, and a power storage system. EXAMPLES
[0178] Below, preferred examples are presented to aid in understanding the present invention. However, these examples are merely illustrative of the present description, and it will be apparent to those skilled in the art that various changes and modifications are possible within the scope and technical spirit of the present description. Naturally, such changes and modifications fall within the scope of the appended claims.
[0179] <Production Example> <Production of negative electrodes> A negative electrode slurry was prepared by adding silicon-based active materials, Si (average particle size (D50): 3.5 μm), SWCNT, MWCNT, and polyacrylamide (PAM) as a binder in the weight ratios shown in Table 1 below to distilled water as a solvent for forming a negative electrode slurry (solid concentration 28 wt%).
[0180] The SWCNTs have a BET specific surface area of 1000 to 1500 m 2 / g, the aspect ratio is 10,000 or more, and the average diameter is 1.0 μm or more. 2 / g level, the average diameter was 10 to 20 μm, and the number of walls was approximately 5 to 20.
[0181] As a specific mixing method, the SWCNTs, MWCNTs, binder, and water were dispersed using a homomixer at 2500 rpm for 30 minutes, and then the silicon-based active material was added and dispersed at 2500 rpm for 30 minutes to prepare a negative electrode slurry.
[0182] The negative electrode slurry was applied to both sides of a copper current collector (thickness: 26 μm) at a rate of 87.7 mg / 25 cm. 2 The negative electrode active material layer (thickness: 33 μm) was formed by coating with a loading amount of 10.0 μm, rolling, and drying in a vacuum oven at 130° C. for 10 hours, and the negative electrode active material layer (thickness: 33 μm) was used as the negative electrode (negative electrode thickness: 41 μm, negative electrode porosity: 40.0%).
[0183] A negative electrode was prepared in the same manner as in Example 1, except that the weight parts of the components in Example 1 were changed to those in Table 1 below.
[0184] [Table 1]
[0185] In Table 1, the parts by weight are based on 100 parts by weight of the total negative electrode composition, and in Table 2 below, the parts by weight are based on 100 parts by weight of the negative electrode active material.
[0186] [Table 2]
[0187] <Comparative Example 7> A negative electrode active material layer composition was prepared by mixing Si (average particle size (D50): 3.5 μm) as a silicon-based active material, a first conductive material, a third conductive material, and polyacrylamide (PAM) as a binder in a weight ratio of 80:10:0.3:9.7. The mixture was added to distilled water as a solvent for forming a negative electrode slurry to produce a first negative electrode slurry (solid concentration 45 wt%).
[0188] The first conductive material is carbon black C (specific surface area: 58 m 2 / g, diameter: 37 nm), and the third conductive material is a carbon nanotube.
[0189] The mixing method was as follows: the first conductive material, the third conductive material, the binder, and water were dispersed using a homomixer at 2500 rpm for 30 minutes, and then the active material was added and dispersed at 2500 rpm for 30 minutes to prepare a slurry.
[0190] The negative electrode slurry was applied to both sides of a copper current collector (thickness: 30 μm) at a rate of 99.65 mg / 25 cm. 2 The negative electrode active material layer (thickness: 37 μm) was formed by coating with a loading amount of 10.0 μm, rolling, and drying in a vacuum oven at 130° C. for 10 hours, and the negative electrode active material layer (thickness: 37 μm) was used as the negative electrode (negative electrode thickness: 41 μm, negative electrode porosity: 40.0%).
[0191] <Comparative Example 8> A negative electrode was manufactured in the same manner as in Comparative Example 7, except that a second conductive material was used instead of the first conductive material. The second conductive material was plate-shaped graphite (specific surface area: 17 m 2 / g, average particle size (D50): 3.5 μm.
[0192] <Comparative Example 9> A negative electrode active material layer composition was prepared using SiO (average particle size (D50): 3.5 μm) as a silicon-based active material, artificial graphite, a first conductive material, a third conductive material, and CMC:SBR as a binder in a weight ratio of 4.779:90.794:0.982:0.018:1.127:2.3. Distilled water was added as a solvent for forming a negative electrode slurry to produce a negative electrode slurry (solid concentration 45% by weight).
[0193] The first conductive material is carbon black C (specific surface area: 58 m 2 / g, diameter: 37 nm), and the third conductive material is a carbon nanotube.
[0194] The mixing method was as follows: the first conductive material, the third conductive material, the binder, and water were dispersed using a homomixer at 2500 rpm for 30 minutes, and then the active material was added and dispersed at 2500 rpm for 30 minutes to prepare a slurry.
[0195] The negative electrode slurry was applied at 9.312 mg / cm2 to both sides of a copper current collector (thickness: 8 μm) as a negative electrode current collector. 2 The coated layer was rolled and dried in a vacuum oven at 130° C. for 10 hours to form a negative electrode active material layer (thickness: 114 μm).
[0196] <Secondary battery manufacturing> LiNi as the positive electrode active material 0.6 Co 0.2 Mn 0.2O2 (average particle size (D50): 15 μm), carbon black (product name: Super C65, manufacturer: Timcal) as a conductive material, and polyvinylidene fluoride (PVdF) as a binder were added in a weight ratio of 97:1.5:1.5 to N-methyl-2-pyrrolidone (NMP) as a solvent for forming a positive electrode slurry to produce a positive electrode slurry (solid concentration 78 wt%).
[0197] The positive electrode current collector was an aluminum current collector (thickness: 12 μm) and the positive electrode slurry was applied to both sides at 537 mg / 25 cm. 2 The coated layer was rolled and dried in a vacuum oven at 130° C. for 10 hours to form a positive electrode active material layer (thickness: 65 μm) to prepare a positive electrode (thickness of positive electrode: 77 μm, porosity: 26%).
[0198] A polyethylene separator was interposed between the positive electrode and the negative electrode of Example 1, and an electrolyte was injected into the separator to produce the secondary battery of Example 1.
[0199] The electrolyte was an organic solvent made by mixing fluoroethylene carbonate (FEC) and diethyl carbonate (DEC) in a volume ratio of 30:70, to which vinylene carbonate was added in an amount of 3 wt % based on the total weight of the electrolyte, and LiPF6 was added as a lithium salt at a concentration of 1 M.
[0200] Secondary batteries were fabricated in the same manner as above, except that the negative electrodes of the Examples and Comparative Examples were used.
[0201] Experimental example 1: Life evaluation of mono cell The secondary battery manufactured as described above was subjected to a life evaluation using an electrochemical charger / discharger to evaluate the capacity retention rate. The secondary battery was subjected to 300 cycles of charging (1.0C cc / CV charging 4.2V 0.05C cut) and discharging (0.5C CC discharging 3.3V cut) at room temperature (25°C), and the capacity retention rate was confirmed.
[0202] The capacity retention rate at the 300th cycle was evaluated using the following formula, and the results are shown in Table 3 below.
[0203] Capacity retention (%) = {(discharge capacity at 300th cycle / (discharge capacity at first cycle)}
[0204] [Table 3]
[0205] Experimental example 2: Cycling resistance increase rate In the test of the above-mentioned Experimental Example 1, the capacity retention rate was measured by charging / discharging (4.2-3.0V) at 0.33C / 0.33C every 100 cycles during the test, and then the resistance was measured by discharging at 2.5C pulse at SOC50, and the resistance increase rate was compared and analyzed.
[0206] For the measurement and evaluation of the resistance increase rate, data at 200 cycles was calculated, and the results are shown in Table 4 below.
[0207] [Table 4]
[0208] As can be seen from Table 3, Examples 1 to 4 of the present invention exhibited superior performance compared to the comparative examples.
[0209] Specifically, in the case of Comparative Example 1, the conductive network was properly formed, but the binder ratio was so low that the connections between the networks were broken, resulting in a decrease in performance.
[0210] In Comparative Example 2, unlike Comparative Example 1, the binder ratio was very high, which seems to have reduced the degree of short circuiting of the interconnection structure between networks. However, the high ratio of the binder, which is a non-conductive material, increased the resistance, resulting in a decrease in performance.
[0211] Comparative Example 3 and Comparative Example 4 are cases where SWCNT or MWCNT is applied alone as the conductive material. Compared with Example 1, only the respective conductive material was excluded and there was no increase in the amount of the conductive material itself, resulting in weakened conductivity and decreased performance.
[0212] Comparative Examples 5 and 6 are cases where an active material in which Si and C are combined is used. In the examples of the present application, all contain one or more selected from the group consisting of SiOx (x = 0) and SiOx (0 < x < 2), and contain 90 parts by weight or more of the SiOx (x = 0) based on 100 parts by weight of the silicon-based active material, that is, it corresponds to the case of using pure Si (Pure Si). In the case of Comparative Examples 5 and 6, maximization of the capacity could not be achieved compared with the examples of the present application. It is a composite of graphite with extremely poor charging performance compared to Si, and since the condition that the evaluation charging C-rate is 1.0C is a very difficult condition to apply to the electrode, it is judged that problems such as lithium plating occurred. Also, when CMC:SBR is used as the binder, it is difficult to improve the performance in silicon-based batteries, and thus it is judged that the performance has decreased rapidly.
[0213] Comparative Examples 7 and 8 correspond to the case where carbon black, which is a dot-shaped conductive material, and plate-shaped graphite, which is a sheet-shaped conductive material, are applied. First, in the case of carbon black, the content of the added composition is high, the viscosity of the slurry becomes very high, which affects the dispersion of carbon black and SWCNT, showing the above results. Also, when plate-shaped graphite is used, since it is not a material that has a great influence on dispersion, there is no problem with the degree of dispersion, but the content of the conductive material increases, the composition ratio of the silicon-based active material decreases, and the electrode weight loading amount increases to achieve the same capacity, resulting in a thicker electrode and decreased performance. For reference, in Comparative Example 7, the thickness of the electrode increased due to the deterioration of conductivity and dispersibility by the conductive material, and the performance was even worse than that of Comparative Example 8.
[0214] Finally, in the case of Comparative Example 9, it was confirmed that the performance was significantly reduced as a result of the mixed electrode of SiO and graphite. This is the result of using graphite, which has a charging performance significantly inferior to that of Si, as the main active material, and it is believed that the result is a problem such as lithium plating, which occurred because the evaluated charging C-rate condition of 1.0C is a very difficult condition to apply to a graphite electrode, and this is the reason why the performance was rapidly reduced. [Explanation of symbols]
[0215] 10 Negative electrode current collector layer 20...Negative electrode active material layer 30 Separator 40...Cathode active material layer 50 Positive electrode current collector layer 100 ···Negative electrode for lithium secondary battery 200 ···Positive electrode for lithium secondary batteries
Claims
1. A negative electrode composition comprising: a silicon-based active material; a linear conductive material; and a negative electrode binder, The silicon-based active material includes one or more selected from the group consisting of SiOx (x=0) and SiOx (0<x<2), and includes 90 parts by weight or more of the SiOx (x=0) based on 100 parts by weight of the silicon-based active material; The linear conductive material includes SWCNT; and MWCNT. The negative electrode composition contains 80 parts by weight or more and 95 parts by weight or less of the silicon-based active material based on 100 parts by weight of the negative electrode composition, The negative electrode composition comprises 3 parts by weight or more and 10 parts by weight or less of the negative electrode binder based on 100 parts by weight of the silicon-based active material.
2. The negative electrode composition of claim 1 , wherein the silicon-based active material has a crystal grain size of 200 nm or less.
3. 2. The negative electrode composition according to claim 1, wherein the linear conductive material is present in an amount of 0.5 parts by weight or more and 10 parts by weight or less based on 100 parts by weight of the silicon-based active material.
4. The negative electrode composition according to claim 1 , wherein the MWCNT is 0.3 parts by weight or more and 6 parts by weight or less, and the SWCNT is 0.1 parts by weight or more and 1.5 parts by weight or less, based on 100 parts by weight of the silicon-based active material.
5. The MWCNT has a specific surface area of 100 m 2 / g to 500m 2 / g, The negative electrode composition according to claim 1 , having a mean diameter of 10 nm or more and 20 nm or less.
6. The SWCNT has a specific surface area of 900 m 2 / g~1500m 2 / g, The negative electrode composition according to claim 1 , having a mean diameter of 50 nm or more and 450 nm or less.
7. The negative electrode composition according to claim 1 , wherein the negative electrode binder comprises at least one selected from the group consisting of a rubber-based binder and a water-based binder.
8. A negative electrode current collector layer; and A negative electrode active material layer comprising the negative electrode composition according to any one of claims 1 to 7, which is formed on one or both sides of the negative electrode current collector layer; A negative electrode for a lithium secondary battery comprising:
9. The thickness of the negative electrode current collector layer is 1 μm or more and 100 μm or less, 9. The negative electrode for a lithium secondary battery according to claim 8, wherein the negative electrode active material layer has a thickness of 10 μm or more and 500 μm or less.
10. Positive electrode; The negative electrode for a lithium secondary battery according to claim 8 ; A separator disposed between the positive electrode and the negative electrode; and Electrolyte; A lithium secondary battery comprising:
Citation Information
Patent Citations
Method for coating silicon negative electrode material with carbon nano tube
CN114361427A
Negative electrode material for lithium secondary battery, and its manufacturing method
JP2005158305A
Nonaqueous electrolyte battery
JP2014112560A
Silicon-containing particle, negative electrode material of nonaqueous electrolyte secondary battery, and nonaqueous electrolyte secondary battery
JP2014192064A
Negative electrode material for power storage device
JP2021131990A